Diaphragm adhesive composition, diaphragm and lithium ion battery
By developing separator adhesive compositions and dot matrix coating technology with appropriate surface tension, the stability of lithium-ion battery separators when temperature rises is solved, the bonding strength and breathability of the battery are improved, and the battery is extended lifespan and improve safety.
Patent Information
- Application Number
- CN202411615272.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing lithium-ion battery separator materials are prone to shrink or melt when the temperature rises, resulting in contact with the positive and negative electrodes, causing short circuits and safety accidents. The existing adhesive coating process affects the breathability and adhesion of the separator, resulting in the battery. The service life is unstable.
Develop a diaphragm adhesive composition with a solid content of 10 wt% to 40 wt%, and the surface tension of the diluent is not less than 28 mN/m. By controlling the particle size and glass transition temperature of polymer particles and adhesive, the binding point Array coating technology forms controllable glue coating points, enhancing the bonding strength and breathability of the diaphragm and electrode material.
Improve the bonding strength between the diaphragm and the electrode material, reduce bubbles and pinhole defects during the coating process, ensure the smoothness and flatness of the diaphragm, improve the performance and reliability of the battery, extend the service life, and reduce the energy consumption and harmful substance emissions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a diaphragm adhesive composition, a diaphragm and a lithium ion battery. Background Art
[0002] As a rechargeable battery with broad application prospects, lithium-ion batteries are widely favored by various industries due to their high energy density, long life, compact size, maintenance-free and environmentally friendly characteristics. It has expanded from mobile phones, laptops and other fields to electric bicycles, electric vehicles, energy storage systems and various portable devices, becoming an ideal mobile power source.
[0003] Lithium-ion batteries are usually composed of a positive electrode, a negative electrode, a separator, an electrolyte and a battery casing. Among them, the separator is one of the key inner components, and its main function is to separate the positive and negative electrodes of the battery to prevent the two from contacting and causing a short circuit. At present, the commonly used separator material in lithium-ion batteries is a polyolefin porous membrane. However, the melting point of this material is low. When the temperature of the battery rises due to internal or external factors, the polyolefin porous membrane may shrink or melt, resulting in direct contact between the positive and negative electrodes, causing a short circuit, which may cause safety accidents such as battery combustion or explosion.
[0004] In order to solve this problem, inorganic particles are usually coated on the surface of the diaphragm substrate using a polymer adhesive to form a composite diaphragm. For example, ceramic particles are coated on the surface of the diaphragm substrate to form a ceramic / polymer composite diaphragm, and the heat resistance of the ceramic particles is used to reduce the thermal shrinkage of the diaphragm. In addition, a layer of polymer adhesive, such as polyvinylidene fluoride (PVDF), is coated on the surface of the diaphragm to enhance the adhesion between the diaphragm and the positive and negative electrodes to ensure the stability of the battery structure.
[0005] At present, the commonly used coating methods are mainly roller coating, spray coating and spot coating. In the glue-coated diaphragm prepared by roller coating, the adhesive particles are evenly distributed on the entire diaphragm and have good adhesion, but the flat adhesive glue will have a significant negative impact on the air permeability of the diaphragm. In the glue-coated diaphragm prepared by spraying, the adhesive is distributed on the diaphragm in the form of small droplets. Due to the uneven size and distribution of the droplets, the adhesion may be unstable, and the air permeability of the diaphragm will also be affected. In the glue-coated diaphragm prepared by spot coating, the adhesive is evenly distributed on the surface of the diaphragm in the form of dots, the adhesion is stable, and the effect on the value-added air permeability of the diaphragm is small. However, the existing battery diaphragm coating process has the problem that the adhesive coating points are easy to spread. The size of the coating points also affects the air permeability of the battery diaphragm and its adhesion to the pole piece, and ultimately affects the stability of the battery service life.
[0006] The adhesive coating point should not spread as much as possible to ensure that the size of the point is controllable. Therefore, a membrane adhesive composition is developed. When the adhesive is used for spot coating, the size of the coating point is controllable and the adhesive does not spread. The coated membrane has excellent adhesion and air permeability. Summary of the invention
[0007] In order to solve the above technical problems, the present invention provides a separator adhesive composition, a separator and a lithium ion battery.
[0008] In a first aspect, the present invention provides a diaphragm adhesive composition, wherein the solid content of the diaphragm adhesive composition is 10wt% to 40wt%, and when the solid content of the diaphragm adhesive composition is diluted to 5wt%, the surface tension of the diluted liquid of the diaphragm adhesive composition is not less than 28mN / m.
[0009] The surface tension of the 5% diluted solution of the diaphragm adhesive composition is not less than 28mN / m, so that the diaphragm adhesive composition is not easy to spread on the substrate, which can prevent the adhesive glue from spreading too quickly on the diaphragm surface, and form controllable, uniformly sized, and evenly distributed glue coating points on the substrate surface, which has little effect on the air permeability of the diaphragm. In addition, the appropriate surface tension can promote the interaction between the diaphragm substrate and the diaphragm adhesive composition, forming stronger physical adsorption, thereby improving the bonding strength between the diaphragm and the electrode material, and enhancing the stability of the battery assembly. The higher surface tension also helps to reduce defects such as bubbles and pinholes that appear during the coating process, and ensure the smoothness and flatness of the diaphragm surface, which is very important for improving the performance and reliability of the battery.
[0010] The solid content of the diaphragm adhesive composition is 10wt%-40wt%, which means that the diaphragm adhesive has good fluidity and is easy to dilute to a lower solid content so as to control the surface density of the diaphragm adhesive coating.
[0011] Preferably, when the solid content of the membrane adhesive composition is diluted to 5wt%, the surface tension of the diluted solution of the membrane adhesive composition is 28-60mN / m. The surface tension of the diluted solution of the membrane adhesive composition includes but is not limited to 28-40mN / m, 40-50mN / m or 50-60mN / m.
[0012] Preferably, the diaphragm adhesive composition comprises polymer particles A and polymer adhesive B, and the solid mass ratio of the polymer particles A to the polymer adhesive B is 100:(3-30).
[0013] In the present application, the solid mass of the polymer particles A refers to the mass of the polymer contained in the polymer particles A, and the solid mass of the polymer binder B refers to the mass of the polymer contained in the polymer binder B.
[0014] Preferably, the particle size of the polymer particles A is 0.2-10 μm.
[0015] Preferably, the glass transition temperature of the polymer particles A is 30-90°C.
[0016] By controlling the particle size and glass transition temperature of polymer particles A, when applied to the diaphragm, the diaphragm has both lower permeability value-added and better peel strength. When the particle size of polymer particles A is too small, it is easy to block the diaphragm pores, resulting in increased permeability value-added, and the peel strength is also weak. When the particle size of polymer particles A is too large, polymer particles A are easy to fall off after coating, and the peel strength is reduced. When the glass transition temperature of polymer particles A is too high, it cannot soften during hot pressing, and the peel strength is low; when the glass transition temperature is too low, it is easy to form a film, resulting in increased permeability value-added of the diaphragm.
[0017] Preferably, the polymer binder B is an aqueous emulsion binder, and the particle size of the polymer particles contained therein is 0.1-1 μm.
[0018] Preferably, the glass transition temperature of the polymer adhesive B is -50~20°C.
[0019] Since the glass transition temperature of polymer binder B is lower than that of polymer particles A and the particle size of polymer binder B is small, polymer particles A and non-conductive particles and other materials can be effectively bonded to the diaphragm substrate, thereby improving the bonding effect.
[0020] By controlling the solid mass ratio of the polymer particles A and the polymer binder B, it is possible to ensure good adhesion and good ion conductivity of the diaphragm. If the proportion of polymer binder B is too high, it is easy to cause pore blockage in the diaphragm and affect the conduction of ions. If the proportion of polymer particles A is too high, it will cause insufficient adhesion between the diaphragm and the electrode sheet.
[0021] In the present invention, both the polymer particles A and the polymer binder B can be obtained by polymerization of monomers containing polymerizable double bonds.
[0022] Preferably, the polymer binder B is selected from at least one of styrene-butadiene latex and polyacrylate emulsion. The polyacrylate refers to the polymer obtained by polymerizing at least one acrylate or methacrylate monomer, and the styrene-butadiene latex is obtained by copolymerizing at least butadiene and styrene. The monomers used to prepare the polymer binder B can also be used to copolymerize the monomers used to prepare the polymer particles A.
[0023] In the present invention, materials such as styrene-butadiene latex and polyacrylate emulsion have good bonding ability, which can effectively bind the diaphragm and polymer particles A tightly, ensure that polymer particles A are not easy to fall off from the diaphragm, ensure the stability between battery components, and help improve the overall performance of the battery. In addition, they have good compatibility with the components in the electrolyte, are not easy to chemically react, and ensure the reliability of long-term use of the battery. The selected materials have good thermal stability and can maintain stable performance in the high temperature environment generated during the battery charging and discharging process, reduce performance degradation caused by temperature increase, and improve the safety and service life of the battery. The above materials are mostly water-based emulsions or solutions. Compared with traditional organic solvent-based adhesives, they are easier to handle and have low volatile organic compounds (VOCs) emissions.
[0024] Preferably, the polymerizable double bond monomer is at least one selected from vinyl monomers, maleate monomers, itaconate monomers, maleimide monomers, (meth)acrylamide monomers, and (meth)acrylate monomers.
[0025] The (meth)acrylamide monomers include acrylamide monomers and methacrylamide monomers, and the (meth)acrylate monomers include acrylate monomers and methacrylate monomers.
[0026] Preferably, the vinyl monomer is selected from vinyl esters, vinyl (thio) ethers, vinyl ketones, vinyl sulfones, acrylonitrile, methacrylonitrile, cyanostyrene, 4-vinylpyridine, 2-vinylpyridine, vinylimidazole, N-vinylpyrrole, N-vinylthiopyrrolidone, ethylene, propylene, butylene, isobutylene, pentene, heptene, diisobutylene, octene, dodecene, octadecene, butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene and 1, At least one of 7-octadiene, cyclohexene, vinylcyclohexene, ethylidene bicycloheptene, cyclopentadiene, cycloheptadiene, dicyclopentadiene, dicycloheptadiene, limonene and indene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotonylstyrene, divinylbenzene, divinyltoluene, divinylxylene, trivinylbenzene, vinylnaphthalene, and p-tert-butylstyrene.
[0027] The maleate monomer is selected from at least one of C1-C12 monoalkyl maleate and C1-C12 dialkyl maleate.
[0028] The itaconate ester monomer is selected from one of itaconate C1-C12 monoester and itaconate C1-C12 diester; The (meth)acrylamide monomer is selected from at least one of (meth)acrylamide, N-methyl(meth)acrylamide, N-butylacrylamide, acetylacetonate acrylamide, N-hydroxymethyl(meth)acrylamide, N,N'-methylenebis[(meth)acrylamide], cinnamamide, N,N-dimethylacrylamide, N,N-dibenzylacrylamide, methacryloylformamide, N-methyl N-vinylacetamide and N-vinylpyrrolidone.
[0029] Preferably, the (meth)acrylate monomer is selected from acrylic acid, methacrylic acid, methacrylates and acrylates, including but not limited to acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, n-octyl acrylate, isooctyl acrylate, isobornyl acrylate, phenoxyethyl acrylate, dicyclopentenyl acrylate, cyclohexyl acrylate, benzyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, carboxyethyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, methacrylic acid At least one of isobornyl methacrylate, phenoxyethyl methacrylate, dicyclopentenyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, polyethylene glycol mono[(meth)acrylate] ester, aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, tert-butylaminoethyl methacrylate, glycidyl (meth)acrylate, tetrahydrofuran (meth)acrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, ethoxylated ethylene glycol diacrylate, ethoxylated ethylene glycol dimethacrylate, allyl methacrylate, diallyl phthalate, diallyl adipate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol diacrylate, pentaerythritol dimethacrylate, pentaerythritol triacrylate, and pentaerythritol trimethacrylate.
[0030] In a second aspect, the present invention provides a diaphragm, comprising the diaphragm adhesive composition as described in the first aspect and a substrate, wherein the substrate may be a diaphragm base film and / or a coated diaphragm with non-conductive particles coated on the base film, and the diaphragm adhesive composition is coated on the substrate by dot matrix coating.
[0031] Preferably, after the diaphragm adhesive composition is applied, the diameter change rate of the adhesive coating points is less than 30%, so as to form coating points that are consistent in size, controllable, and evenly distributed. At the same time, it can prevent the adhesive liquid from diffusing too quickly on the diaphragm surface, which is beneficial to improving the bonding strength between the diaphragm and the electrode.
[0032] Preferably, the diaphragm base film is selected from one of a polyethylene base film, a polypropylene base film, a polypropylene-polyethylene-polypropylene laminated base film, and a non-woven fabric base film.
[0033] Preferably, when the solid content of the diaphragm adhesive composition is diluted to 5wt%, the contact angle between the diaphragm adhesive composition and the diaphragm base film is greater than 30°, so that the diaphragm adhesive composition is not easy to spread on the substrate, and the adhesive glue liquid can be prevented from spreading too quickly on the surface of the diaphragm, and controllable, uniformly sized, and evenly distributed glue coating points are formed on the surface of the substrate, which has little effect on the air permeability of the diaphragm and helps to improve the bonding force between the diaphragm and the electrode.
[0034] Preferably, when the solid content of the diaphragm adhesive composition is diluted to 5wt%, the contact angle between the diaphragm adhesive composition and the diaphragm base film is 30° to 70°. The contact angle between the diaphragm adhesive composition and the diaphragm base film includes but is not limited to 30° to 45°, 45° to 60° or 60° to 70°.
[0035] Preferably, the non-conductive particles in the non-conductive particle diaphragm layer are selected from at least one of hydrated alumina, aluminum oxide, boehmite, silicon dioxide, titanium dioxide, zirconium dioxide, calcium oxide, magnesium oxide, magnesium hydroxide, calcium carbonate, barium titanate, barium sulfate, and heat-resistant organic polymer particles.
[0036] The application of dot matrix coating technology enables the diaphragm adhesive composition to form a coating of uniform size and uniform distribution on the substrate, avoiding the problem of uneven thickness that may be caused by traditional coating methods, and helping to improve the battery's charge and discharge efficiency and cycle stability. It can not only reduce the use and emissions of harmful substances, but also reduce energy consumption.
[0037] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the diaphragm adhesive composition as described in the second aspect or the diaphragm as described in the second aspect.
[0038] Compared with the prior art, the present invention has the following beneficial effects: The surface tension of the 5% dilution of the membrane adhesive composition of the present invention is not less than 28mN / m, so that the membrane adhesive composition is not easy to spread on the substrate, and the adhesive glue can be prevented from spreading too quickly on the membrane surface, and controllable, uniformly sized, and evenly distributed glue coating points are formed on the substrate surface, which has little effect on the air permeability of the membrane and helps to improve the bonding force between the membrane and the pole piece. In addition, the appropriate surface tension can promote the interaction between the membrane substrate and the membrane adhesive composition, forming a stronger physical adsorption, thereby improving the bonding strength between the membrane and the electrode material, and enhancing the stability of the battery assembly. The higher surface tension also helps to reduce defects such as bubbles and pinholes that appear during the coating process, and ensure the smoothness and flatness of the membrane surface, which is very important for improving the performance and reliability of the battery. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a diaphragm adhesive composition, comprising the following steps: Polymer particles A: Weigh 1 part of sodium dodecyl sulfate and 225 parts of deionized water into a stirring container, add 98 parts of methyl methacrylate, 51 parts of butyl acrylate, and 1 part of divinylbenzene, control the stirring speed to 150±50rpm, stir and heat to 74±1°C, then add 0.8 parts of initiator, maintain stirring and react at 74±1°C for 6 hours, then raise the temperature to 79±1°C, continue to react for 3 hours, and obtain an emulsion of polymer particles A with a solid content of 40wt%, an average particle size of 0.2μm, and a glass transition temperature of 30°C.
[0042] Polymer adhesive B: Weigh 1.5 parts of sodium dodecyl sulfate and 225 parts of deionized water into a stirring container, add 88 parts of styrene and 62 parts of butadiene, control the stirring speed to 150±50rpm, stir and heat to 74±1°C, then add 0.8 parts of initiator, maintain stirring and react at 74±1°C for 6 hours, then raise the temperature to 79±1°C, continue the reaction for 3 hours, and obtain a polymer adhesive B emulsion with a solid content of 40wt%, an average particle size of 0.1μm, and a glass transition temperature of 18°C.
[0043] The emulsion of polymer particles A and the emulsion of polymer particles B were mixed at a solid mass ratio of 100:3 to obtain a diaphragm adhesive composition with a solid content of 40wt%. The surface tension of the 5wt% dilution was 29.24mN / m, and the 5wt% dilution was a diaphragm adhesive composition diluted to a solid content of 5wt%.
[0044] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0045] Example 2
[0046] This embodiment provides a method for preparing a diaphragm adhesive composition, comprising the following steps: Step 1: Mix 10 parts of monomer with 0.5 parts of dilauroyl peroxide, stir and dissolve evenly to form a mixed monomer; the monomer used in this embodiment is a mixture of styrene, butyl acrylate, isooctyl acrylate, and divinyl benzene, and the mass ratio is 90:6:3:1; Step 2: Dissolve polyvinyl alcohol 1788 in 90 parts of deionized water to prepare a dispersant aqueous solution with a dispersant concentration of 0.5wt%; Step 3: Pour the mixed solution of the first step into the dispersant aqueous solution of the second step, and homogenize into an oil-water dispersion at a speed of 1000 rpm using a high-speed homogenizer; Step 4: After nitrogen is passed through for 30 minutes, the temperature is raised to polymerize. The polymerization temperature is 75° C. and the polymerization time is 6 hours. After the polymerization is completed, an aqueous dispersion of polymer particles A with a solid content of 10% is obtained.
[0047] The glass transition temperature of the polymer particles A in this embodiment is 90° C., and the particle size of the polymer particles A is 10 μm.
[0048] The preparation process of polymer adhesive B is the same as that of Example 1, except that the amount of sodium dodecyl sulfate used is 0.08 parts, and the monomer composition is a mixture of acrylonitrile, butyl acrylate, and ethylene glycol diacrylate in a mass ratio of 9:90:1.
[0049] The glass transition temperature of the polymer binder B in this example is -41°C and the particle size is 1 μm.
[0050] The emulsion of polymer particles A and the emulsion of polymer particles B were mixed at a solid mass ratio of 100:30 to obtain a diaphragm adhesive composition, with a solid content of 10 wt %. The surface tension of a 5 wt % dilution was 39.35 mN / m.
[0051] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0052] Example 3
[0053] Compared with Example 2, by adjusting the amount of deionized water, the monomer ratio and the speed of the homogenizer, the glass transition temperature of polymer particles A is 40°C, the particle size of polymer particles A is 2 μm, the particle size of polymer binder B is 0.5 μm, and the glass transition temperature is -41°C. The solid content of the diaphragm adhesive composition is 25wt%, and the mass ratio of polymer particles A to polymer binder B is 100:15. The surface tension of the 5wt% dilution is 31.28mN / m.
[0054] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0055] Example 4
[0056] Compared with Example 3, the glass transition temperature of the polymer particles is 50°C, the particle size of polymer particles A is 4 μm, the solid content of the diaphragm adhesive composition is 15 wt %, and the mass ratio of polymer particles A to polymer adhesive B is 100:15. The surface tension of the 5 wt % dilution is 31.39 mN / m.
[0057] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0058] Example 5
[0059] Compared with Example 3, the glass transition temperature of the polymer particles is 60°C, the particle size of polymer particles A is 5 μm, the solid content of the diaphragm adhesive composition is 15 wt %, and the mass ratio of polymer particles A and polymer adhesive B is 100:15. The surface tension of the 5 wt % dilution is 30.46 mN / m.
[0060] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0061] Example 6
[0062] Compared with Example 3, the glass transition temperature of the polymer particles is 70°C, the particle size of polymer particles A is 6 μm, the solid content of the diaphragm adhesive composition is 15 wt %, and the mass ratio of polymer particles A and polymer adhesive B is 100:15. The surface tension of the 5 wt % dilution is 30.84 mN / m.
[0063] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0064] Example 7
[0065] Compared with Example 3, the glass transition temperature of the polymer particles is 80°C, the particle size of polymer particles A is 8 μm, the solid content of the diaphragm adhesive composition is 15 wt %, and the mass ratio of polymer particles A and polymer adhesive B is 100:15. The surface tension of the 5 wt % dilution is 31.32 mN / m.
[0066] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0067] Example 8
[0068] Compared with Example 1, the glass transition temperature of the polymer particles is 30°C, the particle size of polymer particles A is 9 μm, the solid content of the diaphragm adhesive composition is 15 wt %, and the mass ratio of polymer particles A and polymer adhesive B is 100:15. The surface tension of the 5 wt % dilution is 30.95 mN / m.
[0069] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0070] Example 9
[0071] Compared with Example 3, the diaphragm adhesive composition is the same, except that the diaphragm adhesive is coated on the surface of the coated diaphragm containing the boehmite coating, and the thickness of the boehmite coating is 2 μm.
[0072] Comparative Example 1 Compared with Example 3, the glass transition temperature of the polymer particles is 20° C., and the remaining steps are the same as in Example 3. The surface tension of the 5 wt % dilution is 31.33 mN / m.
[0073] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0074] Comparative Example 2 Compared with Example 3, the glass transition temperature of the polymer particles is 100° C., and the remaining steps are the same as in Example 3. The surface tension of the 5 wt % dilution is 31.52 mN / m.
[0075] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0076] Comparative Example 3 Compared with Example 3, the particle size of polymer particles A is 0.1 μm, and the remaining steps are the same as in Example 3. The surface tension of the 5wt% dilution is 30.76 mN / m.
[0077] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0078] Comparative Example 4 Compared with Example 3, the particle size of polymer particles A is 11 μm, and the remaining steps are the same as in Example 3. The surface tension of the 5 wt % dilution is 30.93 mN / m.
[0079] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0080] Comparative Example 5 Compared with Example 3, the surface tension of the diluted solution of the diaphragm adhesive composition is 26.89 mN / m, and the remaining steps are the same as those in Example 3.
[0081] The diaphragm adhesive composition is coated on the surface of the diaphragm base film.
[0082] Comparative Example 6 Compared with Comparative Example 5, the diaphragm adhesive composition is the same, except that the diaphragm adhesive is coated on the surface of the coated diaphragm containing the boehmite coating, and the thickness of the boehmite coating is 2 μm.
[0083] In all the above embodiments and comparative examples, the membrane adhesive composition is coated on the surface of the substrate in a dot matrix manner, the design diameter of the coating point is 300 μm, and the surface density of the membrane adhesive composition is 0.2 g / m 2 .
[0084] This embodiment also provides a lithium-ion battery, which uses the separator in this embodiment.
[0085] The battery preparation method is as follows: the negative electrode sheet, the positive electrode sheet, the electrolyte and the separator are assembled into a battery.
[0086] The polymers of Examples 1-9 and Comparative Examples 1-6 were characterized and tested for performance. The test results are shown in Table 1.
[0087] Particle size: The particle size of the polymer particles was measured using a laser particle size analyzer (Zhuhai OMEC Instrument Co., Ltd., model: LS-909E).
[0088] Glass transition temperature: The glass transition temperature Tg of the separator adhesive composition was measured using a differential scanning calorimeter (Shanghai Qunhong Instrument Equipment Co., Ltd., model: DSC-100); Surface tension test: The surface tension of the membrane adhesive composition dilution liquid was tested at 23±1°C using a platinum plate method, with the unit being mN / m.
[0089] Peel strength test: The coated diaphragm and negative electrode plate prepared by the scheme of the present invention were cut into 20mm*100mm strips respectively, cold pressed for 60s at 95°C and 2MPa, and subjected to a 180° peel strength test using an electronic tensile testing machine. The test results were taken as the average value of 3 samples.
[0090] The test method for air permeability value-added is: refer to the air permeability test in GB / T 36363-2018 "Polyolefin separator for lithium-ion batteries": Cut three pieces of membrane from the film roll at 150mm intervals in the longitudinal direction. If the membrane width is ≥100mm, the sample size is 100mm×100mm. If the membrane width is <100mm, the sample size is 100mm×membrane width. Place the membrane in the test head of the permeability meter suitable for the test range to test the permeability time. Take the average value of the three test results as the permeability time of the membrane, in s / 100cc.
[0091] The membrane permeability increment is the difference between the permeability time of the membrane after the adhesive is applied and the permeability time of the membrane before the adhesive is applied, and the unit is s / 100cc; Contact angle test: The contact angle of 5wt% dilution was tested using a contact angle meter. 3μl of 5wt% dilution was dropped onto the diaphragm base film and photographed after 5 seconds. The unit is °.
[0092] Glue dot diameter change rate: After the diaphragm coated with adhesive is dried, measure the increase in the diameter of the adhesive dot relative to the theoretical diameter, that is, (actual measured diameter - 300) / 300*100%.
[0093] Table 1
[0094] The test results show that when the surface tension of the glue diluent is above 28mN / m, the change rate of the glue spot diameter after the diaphragm adhesive composition is coated and dried is small. When the surface tension is too low, the change rate of the glue spot diameter is large, and the air permeability value-added becomes larger. When the particle size of polymer particles A is between 0.2-10μm and the glass transition temperature is between 30-90℃, the diaphragm has both lower air permeability value-added and better peel strength. When the particle size of polymer particles A is too small, it is easy to block the diaphragm pores, resulting in increased air permeability value-added, and the peel strength is also weak. When the particle size of polymer particles A is too large, polymer particles A are easy to fall off after coating, and the peel strength is reduced. The glass transition temperature of polymer particles A is too high, and it cannot be softened during hot pressing, and the peel strength is low; while if the glass transition temperature is too low, it is easy to form a film, resulting in a larger air permeability value-added of the diaphragm.
[0095] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A diaphragm adhesive composition, It is characterized in that The solid content of the diaphragm adhesive composition is 10wt% to 40wt%. When the solid content of the diaphragm adhesive composition is diluted to 5wt%, the surface tension of the diluted solution of the diaphragm adhesive composition is not less than 28mN / m.
2. The diaphragm adhesive composition according to claim 1, It is characterized in that When the solid content of the diaphragm adhesive composition is diluted to 5 wt %, the surface tension of the diluted solution of the diaphragm adhesive composition is 28-60 mN / m.
3. The diaphragm adhesive composition according to claim 2, It is characterized in that The diaphragm adhesive composition comprises polymer particles A and polymer adhesive B, and the solid mass ratio of the polymer particles A to the polymer adhesive B is 100:(3-30).
4. The diaphragm adhesive composition according to claim 3, It is characterized in that The particle size of the polymer particles A is 0.2-10 μm, and the glass transition temperature of the polymer particles A is 30-90° C.
5. The diaphragm adhesive composition according to claim 3, It is characterized in that The polymer adhesive B is an aqueous emulsion type adhesive, the particle size of the polymer particles contained therein is 0.1-1 μm, and the glass transition temperature of the polymer adhesive B is -50~20°C.
6. A diaphragm, It is characterized in that The diaphragm comprises a substrate and a diaphragm adhesive composition as described in any one of claims 1 to 5, wherein the substrate is a diaphragm base film and / or a coated diaphragm with non-conductive particles coated on the diaphragm base film, and the diaphragm adhesive composition is coated on the substrate by dot matrix coating.
7. The diaphragm according to claim 6, It is characterized in that When the solid content of the diaphragm adhesive composition is diluted to 5 wt %, the contact angle between the diaphragm adhesive composition and the diaphragm base film is greater than 30°.
8. The diaphragm according to claim 7, It is characterized in that When the solid content of the diaphragm adhesive composition is diluted to 5 wt %, the contact angle between the diaphragm adhesive composition and the diaphragm base film is 30° to 70°.
9. The diaphragm according to claim 8, It is characterized in that The change rate of the diameter of the coating point of the diaphragm adhesive composition on the substrate is less than 30%.
10. A lithium ion battery, It is characterized in that The lithium-ion battery comprises the separator adhesive composition according to any one of claims 1 to 5, or the separator according to any one of claims 6 to 9.
Citation Information
Patent Citations
Dotted coating diaphragm slurry, composite diaphragm and preparation method of composite diaphragm
CN110911620A
Adhesive, preparation method of adhesive, negative plate and preparation of negative plate
CN111978475A
Glued diaphragm as well as preparation method and application thereof
CN116014365A
Separator for power storage device
CN117480681A
Binder for secondary battery, preparation method thereof, diaphragm, battery monomer, battery and electric device
CN118791991A
